Prediction of hydraulic jump characteristics in a closed conduit using numerical and analytical methods. (December 2021) - Maryami, Ehsan; Mohammadpour, Reza; Beirami, Mohammad Karim; Haghighi, Ali Torabi
Abstract: The hydraulic jump is an economical alternative to dissipate energy in the conduit and to reduce erosion at the culvert outlet. In the literature, very limited studies have been reported on the performance of hydraulic jump in a closed conduit. The innovation of this research is to employ a numerical method for the estimation of the hydraulic jump characteristics in a closed conduit with different positive slopes ( S 0 ). The analytical method was used to develop several equations for hydraulic jump and the provided results were compared with the numerical method. The results indicate that the numerical method predicts the flow depth ratio after conduit with higher accuracy (error less than 5%) in comparison to the analytical method (error less than 10%). Furthermore, in the slope of 0.00, the energy loss increases by 16% with increasing the Froude number from 4.617 to 5.562 while this value is 23% and 22% for slopes of 0.01 and 0.02, respectively. Finally, several equations were developed for the prediction of hydraulic jump characteristics in terms of Fr 1, S 0, and conduit depth ( D ). Highlights: The numerical and analytical methods were used to determine the hydraulic jump in a conduit. Several equations were developed for the prediction of hydraulic jump characteristics. Results indicate that the numerical method is able to predict the flow depth with higher accuracy. The energy loss ratio and sequence depth increase with increasing Froude number.